Application Of Utaut2 Model To Explain The Acceptability Of Web-Based Multimodality Learning Media - Linda Ariesandi; Yunus Abidin; Dede Tri Kurniawan (Journal of Future Education, 2026)
This research aims to determine the acceptance and use of web-based multimodality learning media with the UTAUT2 model. Web-based multimodality learning media is a media that is needed for educators as a 21st century learning innovation. UTAUT2 is a development of the UTAUT model implemented by Venkates. The variables contained in UTAUT2 are performance expectations, business expectations, social influence, facility conditions, hedonic motivation, price values, and habits. Data was collected from 100 respondents after filling out a questionnaire with 40 questions asked. The population of this research are teachers in the West Java region. In processing the data in this research, SmartPLS 3 was used to determine the quality, validity and reliability of the data collected. The results of this research show that of the seven hypotheses proposed, two hypotheses can be accepted, namely facilitating conditions and social influence on user interest (behavioral intention).